Queering Dixie: The challenging of social norms in contemporary gay fiction - Evans, Richard (University of Ottawa (Canada), 2003)
This thesis inquires into how three contemporary gay and lesbian Southern authors under the age of 35 challenge and question the established notions of gender, class, sexuality, and religion in the American South. The three authors under consideration are Christopher Rice ( A Density of Souls), Poppy Z. Brite (Drawing Blood), and Julia Watts (Finding H. F.). By examining the works of a gay man from New Orleans (an urban area), a bisexual woman originally from Georgia now living in New Orleans (urban/rural spheres), and a lesbian from small-town Kentucky (rural space), respectively, the notion of the security and power of an established urban "queer" community reaching out to positively influence the rural space is explored. The traditional expectation within gay and lesbian writing of the necessity to flee the repressive rural space for the liberation of the urban Mecca is thus both explored and challenged by these three young authors.
Keywords: Literature, American.